Identities, internship programs and teaching: Discursive analysis of undergraduate student statements from a Federal University of Rio Grande do Sul, Brazil - Sandra Regina de Moura; Dóris Maria Luzzardi Fiss (Arizona State University, 2017)
This article analyzed, from the perspective of six graduates of the Course of Pedagogy (FACED / UFRGS), the effects of the obligatory curricular internship and its role in the formation of teaching identities. This qualitative research carried out in 2014 involved listening to the voices of graduates in the period of compulsory curricular traineeship in a municipal public school system located in the city of Porto Alegre (Rio Grande do Sul, Brazil). By means of a focal group, the authors addressed themes of stage and professional identity, concepts developed by Maurice Tardif and Danielle Raymond, António Nóvoa, Selma Garrido Pimenta and Maria Socorro Lima. Drawing on the discursive perspectives of Michel Pêcheux, and highlighting contributions offered by Eni Orlandi, the discourse analysis of the graduates' speech produced several themes that influenced the formation of the graduates' educational identities, including teaching as collaborative work, "human teaching", and experiences of autonomy and transition, and that referred to the obligatory curricular stage as a space for learning, reflection about practice, and the space of praxis. In addition, six trainees perceived their internship as an experience that produced changes in their ways of thinking and becoming teachers. Thus, discursive analysis of internship graduates within the time and spaces of teacher formation may can contribute to other designs for schooling and education, considering the relevance of the dynamic conditions of dialogue at this specific stage.